Examining the Relationship between E-Commerce Experience and Repurchase Intention in China: The Mediating Effect of Perceived Value - Cao, Mingxiang; Saidin, Zainil Hanim; Md Harizan, Siti Haslina (International Review of Management and Marketing, 2026)
This study investigates whether consumers’ e-commerce experience strengthens repurchase intention in China and whether this relationship operates through perceived value. By modeling the experience–value–intention mechanism, the study clarifies how platform-level experience translates into repeat purchasing intentions in a market characterized by intense competition and low switching frictions. A cross-sectional survey using a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree) was administered to Chinese online shoppers. A total of 450 questionnaires were distributed and 370 were returned (response rate = 82.2%). After screening for incomplete and low-quality responses, 342 valid responses were retained for analysis (effective response rate = 76.0%). The research model was evaluated using partial least squares structural equation modeling (PLS-SEM) in SmartPLS with 5,000 bootstrap resamples. Results show that e-commerce experience significantly influences perceived value (β = 0.52, p < 0.001), which subsequently predicts repurchase intention (β = 0.55, p < 0.001). Mediation analysis confirms a significant partial mediating effect, and the model explains 43.8% of the variance in repurchase intention. The study contributes to e-commerce loyalty research by emphasizing that experience-based differentiation primarily drives repeat purchase intention through consumers’ value assessments. The findings suggest that improving end-to-end experience (information quality, transaction convenience, fulfillment transparency, and service recovery) should be evaluated by its contribution to perceived value rather than by isolated interface metrics.